Peranan Konseling Dalam pemberian bantuan Pada Ranah Kepolisian - Mona; Margaretha Tri Astuti; Nur Aliza; Yeni Juwita; Daniel Ade. K; Affan Yusra (CV. Multi Kreasi Media, 2022)
The counseling process itself is needed to carry out a health examination that includes mental, as well as physical, a focus on well-being which is recommended to reduce the stigma of consultation for problems, benefiting the individual directly; make financial savings for the organization (eg, reducing sick absenteeism); and reduce absenteeism pressure on other staff. The research method that will be used in this case is a literature review where through the Google Scholar database using the keywords